Implementasi Cloud Computing Cluster Menggunakan Ovirt Untuk Layanan Web - Muhammad Arif Fadhly Ridha; Thesa Nabila Balqis (Jurnal Komputer Terapan, 2023)
Cloud Computing Cluster consists of different servers, working together to ensure that downtime of critical resources is reduced to a minimum with the aim of ensuring that critical resources reach maximum availability which is known as high availability. For the implementation of cluster cloud computing requires a platform that has tools that can support these needs. One platform that can be used is Ovirt. Ovirt is an open source based virtualization solution, designed to manage the entire infrastructure of an agency. Ovirt uses the KVM hypervisor and is built on top of several other community projects, including libvirt, Gluster, PatternFly, and Ansible. Technically Ovirt can have Clustering technology and have High Availability in environments that use more than one hypervisor. Its usefulness is that if one hypervisor has a problem, the Virtual Machine (VM) in it can move to another hypervisor. The result of this research is the achievement of high availability on web server services where web services can still be accessed when two nodes are turned off and when one of the servers is turned off. CPU usage increases when there are multiple number of http requests when multiple nodes are shut down and also when one of the physical servers is shut down, the same thing happens to memory usage which increases by 1% when multiple nodes are shut down and also when one of the physical servers is shut down